Legal Reforms and Strategic Adaptations: An Empirical Perspective on TRIPS and the Indian Pharmaceutical Industry - Alam, Teg; Rastogi, Rupesh (New Advances in Business, Management and Economics Vol. 4, 2025)
Intellectual property (IP) protection in India dates back to the British colonial era when a comprehensive legal framework was established to safeguard such rights. During this period, the pharmaceutical industry benefited from a robust protection system under British law, which, while fostering innovation, also contributed to high medicine prices in the country. In response, the Indian Patent Act of 1970 was introduced to promote the domestic pharmaceutical industry and ensure the availability of affordable medicines by allowing only process patents for pharmaceuticals. This approach significantly altered the industry landscape until subsequent amendments were made to meet the mandatory requirements of the World Trade Organization (WTO) and the Trade-Related Aspects of Intellectual Property Rights (TRIPS) Agreement. This paper explores the impact of these legal changes on the Indian pharmaceutical sector. It is based on secondary data derived from the annual reports of prominent pharmaceutical companies such as Aurobindo, Cipla, Lupin, Ranbaxy, and Dabur. The study utilizes GAP analysis to compare the financial performance of these companies during the pre-TRIPS and post-TRIPS periods, with additional data validation conducted using the SPSS statistical package. The findings reveal a marked improvement in the financial position of Indian pharmaceutical companies in the post-TRIPS era. This improvement is attributed to increased investments in research and development (R&D) and a strategic emphasis on strengthening core competencies. Overall, the study offers valuable insights into how evolving legal frameworks have reshaped the industry's competitive landscape, highlighting the critical role of adaptive strategies in sustaining growth and global competitiveness in the modern pharmaceutical market.